68Ga-FAPI-04 Accumulation in Myocardial Infarction in a Patient With Neuroendocrine Carcinoma. (December 2020) - Zhu, Wenjia; Guo, Fan; Wang, Yawen; Ding, Haiyan; Huo, Li
Abstract : Abstract: We present a case of a 64-year-old man with neuroendocrine carcinoma. Incidental findings were demonstrated on 68 Ga-FAPI-04 PET/CT in the inferior wall of left ventricle. A diagnosis of old myocardial infarction was made based on typical electrocardiogram change. Our case suggests that 68 Ga-FAPI PET/CT, as a noninvasive method to reflect fibroblast activation, is potentially feasible for assessment of cardiac remodeling after myocardial infarction in a clinical setting.